Patient Satisfaction: Evaluating Nursing Care for Patients Hospitalized with Cancer - Rozina Asghar, Mansoor Ghani, Nazi Noor, Sumaira Sharif, Ayyazada Farhana, Tahira Khatoon, (Pakistan Journal of Medical & Health Sciences, 2022)
Patient’s satisfaction is an indicator of quality care and it encompasses the different aspects of nursing care leading to cancer patient’s satisfaction like information given by nurses. Aim: To assess the level of satisfaction with nursing care among hospitalized cancer patients. Study design: Cross-sectional descriptive study. Methodology: A sample of 158 patients in two hospitals was selected from Jinnah hospital Lahore and INMOL by using method of non-probability convenient sampling. Data was collected by adopted questionnaire. Data was analyzed by SPSS software, version 20. Chi square was used for qualitative variables like satisfaction, educational status. A p-value of ≤ 0.05 was considered as statistically significant. Results: The results of this study indicated that a majority of the cancer patients were satisfied with different aspects of nursing care such as information given by nurses, 60.28% of patients were satisfied but interpersonal relations between nurses and patients were found to have mixed response as only 60.61% patients were satisfied. Regarding the technical quality of nurse 68.07% of patients were satisfied. Practical Implication: This study identified the lacking among health care providers regarding nursing care that make a barrier for patient’s satisfaction and helped in Program planning for monitoring and improving the nursing care services at health care setups. Conclusion: We concluded that majority of the patients were satisfied by the nursing care but there is a need to improve the information given by nurses and interpersonal relationship in the nursing care provided by the selected hospitals to improve patients’ overall satisfaction. Keywords: Patient Satisfaction, Nursing Care and Cancer.